Global Trends in Education: Emerging Practices and Innovations - Oliver Brown (Bright Mind Publishing, 2025)
In recent years, education systems around the world have undergone significant transformations, shaped by global trends in technology, pedagogy, and social demands. This paper explores the key global trends influencing education in the 21st century, including digital learning, personalized education, the rise of artificial intelligence (AI), global citizenship education, and inclusivity in educational practices. By analyzing the impact of these trends, the paper discusses their potential to reshape educational outcomes and equity across diverse contexts. The study examines research findings from 2024 to identify common patterns and challenges, offering insights into how education systems can adapt to the evolving global landscape.
Keywords: Global Trends, Education, Digital Learning, Personalized Education, Artificial Intelligence (AI), Global Citizenship, Inclusivity, Educational Equity.